Towards A Framework for E-Medicine Knowledge Management in Uganda, Nigeria and Ethiopia - Isabalija, Stephen Robert; Mayoka Kituyi, Geoffrey (International Journal of Contemporary Applied Researches, 2018)
This study therefore was intended to fill-in the e-medicine knowledge management gap in Africa by developing a theoretical framework that would help in harnessing utilizing and preserving e-medicine using telemedicine platforms in Africa. This paper proposes a knowledge management framework to ensure Knowledge sharing and management which will go a long way in solving the problems of resource-poor settings in SSA. A qualitative research design was used, although some quantitative methods were used. Structural equation modeling was used to develop and test the new framework. Findings indicate that knowledge management practices strongly influenced the sustainable e-medicine outcomes in Ethiopia, Nigeria, and Uganda. The study did not survey many of the actual users of e-medicine; we mainly worked with doctors, nurses IT specialists and administrators. This study correlates with Uwe (2002) about the “brain gain” hypothesis that seeks to reverse the conclusion of brain drain by many scholars and deduces that through a remigration of elites with good knowledge management practices, the human capital stock will increase and so does the potential growth of the developing countries. This study also reveals that the notion of information science researchers on e-medicine emphasis on ICT;s, this study recognizes that ICT is not sufficient to ensure improvement in the well-being of the underprivileged ,rather, application of ICT should be supplemented with appropriate social protection policies which would enable the poor to actually benefit from information/knowledge. knowledge management in the health sector remains a key factor in sustainability of e-medicine. The framework presented in this paper will provide a good guiding basis for managing e-medicine knowledge in developing countries.
Keywords: E-Medicine; Telemedicine; Knowledge Management; Knowledge Sharing; Knowledge Transfer; Africa